COMPARISON OF OSL AND TL DOSEMETERS WITH DATA COLLECTED AT THE MT25 CYCLIC ELECTRON ACCELERATOR. Issue 9 (22nd August 2022) - Cimmino, Anna; Ambrožová, Iva; Motta, Silvia; Versaci, Roberto; Olšovcová, Veronika; Chvátil, David; Olšanský, Václav; Truneček, Roman; Velyhan, Andriy; Stránský, Vojtěch; Šolc, Jaroslav
Abstract: The Microtron MT25 is a cyclic electron accelerator with a Kapitza resonator, maximum beam energy of 25 MeV, standard repetition frequency of 423 Hz, pulse length of 3.5 μs and mean current of 30 μA. Studies at conventional particle accelerators allow to understand the response of dosemeters in known and controllable radiation fields. Subsequently, it is possible to develop models and predict their behavior in complex radiation fields, such as those generated at laser and FLASH facilities. Therefore, response of thermally and optically stimulated luminescence detectors outside of the beam was studied at the Microtron MT25. The detectors were placed on a Plexiglas phantom inside a lead and iron bunker to shield-off background radiation. In addition, GAFChromic™ films and track detectors were used. Two irradiations were performed: with and without an 8-cm thick polyethylene moderator. This paper presents a comparison of the responses of the different detection systems.